Cistercian stories for nuns and monks : the sacramental imagination of Engelhard of Langheim - Newman, Martha G., 1958- (Middle Ages series., 2020)
"This investigation of Engelhard of Langheim's writings lies at the intersection of intellectual and social history, and it combines historical methods with the theoretical interventions encouraged by the field of religious studies. Since Engelhard's compositions have not been fully edited, the medievalist's tasks of manuscript transcription, translation, and analysis form the foundation for this study. This close reading of Engelhard's texts identifies the liturgical and biblical resonances in his language, examines the gendered aspects of his expressions, and compares his stories to those of his Cistercian contemporaries. Furthermore, Newman locates Engelhard's sacramental spirituality within his monastic environment, unearthing his networks of friends and patrons, and exploring his reactions to the social and intellectual changes of his period. Through this process of comparison and contextualization, her work considers the place of the sacraments within Cistercian life as well as investigating monastic conceptions of sight and vision, the role of Mary in Cistercian devotion, and aspects of everyday life that are seldom accessible. Finally, Newman employs theories of reader reception and cognitive blending to analyze how the nuns of Wechterswinkel may have received Engelhard's text, and she draws on insights from anthropology and cognitive science that illuminate how people learn to believe. This study engages with conversations within the field of religious studies that trace the genealogy of religion, and it suggests the importance of understanding conceptions of faith in the period before the Reformation. By uncovering a religiosity of late twelfth-century nuns and monks that is seldom visible, this book explores the processes of imagination and practice that make conceptions of the unseen and the transcendent seem real"--